An Observational Study on Early Dyadic Interactive Behaviors of Mothers With Early-Preterm, Late-Preterm, and Full-Term Infants in Malawi. (February 2020) - Gondwe, Kaboni Whitney; Brandon, Debra; Yang, Qing; Malcolm, William F.; Small, Maria J.; Holditch-Davis, Diane
Abstract : Background: Mother–infant interactions are necessary for infant growth and development. However, preterm birth is associated with less positive mother–infant interactions than full-term birth. Malawi has the highest preterm birth rate in the world, but studies of the mother–infant relationship in Malawi are limited and studies that observed mother–infant interactions could not be located. Purpose: This study explored mother–infant interactions among Malawian mothers of early-preterm, late-preterm, and full-term infants. Methods: This observational study explored maternal and infant interactive behaviors. We recruited 83 mother–infant dyads (27 early-preterm, 29 late-preterm, and 27 full-term dyads). Findings: Mothers of early-preterm infants looked at and rocked their infants less, and their infants looked at their mothers less, than mothers of either late-preterm infants or full-term infants. The infants in all groups were asleep most of the time, which contributed to low levels of interactive behaviors. Factors that were related to infant behaviors included marital status, maternal occupation, maternal education, infant medical complications, infant gender, history of neonatal deaths, and multiple births. Implications for Practice: Our findings provide evidence about the need to encourage mothers to engage interactive behaviors with their infants. Implications for Research: Future studies of factors that contribute to positive interactions in Malawi are needed. Abstract : Supplemental Digital Content is Available in the Text.